State and the Concept of Law and Politics - Patchim, Thanapat; Kongritrajun, Rungphop (Suan Dusit Graduate School Academic Journal, 2021)
This article explained the relation between state and law and politics. The idea began with a consideration on state, which emerged as the true existence of law. Meanwhile, the general explanation to the state usually treated state as social unit isolated from law. That was to say, state appeared as the unit of government as the community of the gathering of humans - the autonomous social animals in itself to which its existence preceded the law. Law was initiated as a result of the state as the existence of legal order and law appeared as "the form of government" Despite the different forms of government in each state, they shared the conditions and means of creating social and legal orders. Regardless of the epoch of modernity, spaces, and different cultures, it was implied that "law" was a technical aspect of the society that had its specific form of coercion of power. Consequently, despite differential relations between ancient and modern laws and difference in terms of nationalities and languages, the common features of law consisted of a social technique which was created for men to have a desired collective action and of the objective study of the disciple of law and politics, which are incapable of completing all aspects, without concerning on a crucial factor, that is, a consideration on statehood and political procedure, which had a relation that led to the reality of political community, which was the objective of law as the discipline to shed light on all legal norms created by each action of sociable men.